Unveiling Majorana quasiparticles by a quantum phase transition: Proposal of a current switch - Dessotti, F. A. [UNESP]; Ricco, L. S. [UNESP]; Marques, Y. [UNESP]; Guessi, L. H. [UNESP]; Yoshida, M. [UNESP]; Figueira, M. S.; De Souza, M. [UNESP]; Sodano, Pasquale; Seridonio, A. C. [UNESP] (American Physical Society (APS), 2016)
We propose a theoretical approach based on an interferometer composed by two quantum dots asymmetrically coupled to isolated Majorana quasiparticles (MQPs), lying on the edges of two topological Kitaev chains, respectively, via couplings (t+Δ) and (Δ-t). This setup enables us to probe MQPs in a quite distinct way from the zero-bias peak feature. Most importantly, the system behaves as a current switch made by two distinct paths: (i) for the upper dot connected to both chains, the device perceives both MQPs as an ordinary fermion and the current crosses solely the lower dot, since current in the upper dot is prevented due to the presence of the superconducting gap; and (ii) by suppressing slightly the hybridization of the upper dot with one chain, the current is abruptly switched to flow through this dot, once a trapped electron as a bound state in the continuum (BIC) [Phys. Rev. B 93, 165116 (2016)2469-995010.1103/PhysRevB.93.165116] appears in the lower dot. Such a current switch between upper and lower dots characterizes the quantum phase transition (QPT) proposed here, being the ratio t/Δ the control parameter of the transition. This QPT is associated with a change from an ordinary fermionic excitation regime to a MQP in the interferometer, which enables not only the fundamental revealing of MQPs, but also yields a current switch assisted by them.